The underneath - Appelt, Kathi, 1954- (Atheneum Books for Young Readers, 2010)
A calico cat about to have kittens befriends a hound dog, Ranger, who urges her to hide underneath the porch of his dilapidated house to raise her kittens. Ranger warns the cat about the man named Gar-Face who lives in the house will likely use the kittens as alligator bait. Soon one kitten becomes very curious and ventures out, setting off a chain of remarkable events.